CD27low Natural Killer Cells Prolong Allograft Survival in Mice by Controlling Alloreactive CD8+ T Cells in a T-Bet–Dependent Manner. Issue 2 (February 2015) - Lantow, Margareta; Eggenhofer, Elke; Sabet-Baktach, Manije; Renner, Philipp; Rovira, Jordi; Koehl, Gudrun E.; Schlitt, Hans J.; Geissler, Edward K.; Kroemer, Alexander
Abstract : Background: Natural killer (NK) cells play a dichotomous role in alloimmune responses because they are known to promote both allograft survival and rejection. The aim of this study was to investigate the role of functionally distinct NK cell subsets in alloimmunity with the hypothesis that this dichotomy is explained by the functional heterogeneity of distinct NK cell subsets. Methods: Because T-bet controls the maturation of NK cells from CD27 high to terminally differentiated CD27 low NK cells, we used Rag −/− T-bet −/− mice that lack mature CD27 low NK cells to study the distinct roles of CD27 low versus CD27 high NK cells in a model of T cell–mediated skin transplant rejection under costimulatory blockade conditions. Results: We found that T cell–reconstituted Rag1 −/− recipients (possessing CD27 low NK cells) show significantly prolonged allograft survival on costimulatory blockade when compared to Rag1 −/− T-bet −/− mice (lacking CD27 low NK cells), indicating that CD27 low but not CD27 high NK cells enhance allograft survival. Critically, Rag1 −/− T-bet −/− recipients showed strikingly increased alloreactive memory CD8 + T cell responses, as indicated by increased CD8 + T cell proliferation and interferon-γ production. Therefore, we speculated that CD27 low NK cells directly regulate alloreactive CD8 + T cell responses under costimulatory blockade conditions. To test this, we adoptively transferred CD27 low NK cells into Rag1 −/− T-bet −/− skin transplant recipients and found that the CD27 low NK cells restore better allograft survival by inhibiting the proliferation of alloreactive interferon-γ + CD8 + T cells. Conclusions: In summary, mature CD27 low NK cells promote allograft survival under costimulatory blockade conditions by regulating alloreactive memory CD8 + T-cell responses. Abstract : Using a fully allogeneic skin transplant model and adoptive transfer of NK cells, Lantow et al report that it is the mature CD27low NK cell subset that promotes allograft survival under co-stimulatory blockade by regulating alloreactive memory CD8+ T cell responses. Supplemental digital content is available in the text.